A business plan: TCM health-preservation club - Li Jinnan (2019)
This master project has the objective to develop a Business Plan which will enable the launch of a TCM health-preservation club which will offer TCM method servicess for modern female consumers in Anyang area, Henan Province, China. The health problems of modern females are rising rapidly due to the unhealthy lifestyle and environmental problems and the TCM in this area has highly potential market, especially targeting for females. However, based on a ground study, we quickly realised that all clinic or club look alike and propose the same local specialties with less professional and services level. By catching the markt opportunities, we analyse the current market with macro data and comparing them with field data I acquired with a questionnaire and a field trip, I decided to launch a TCM club - the new serves intends to change female relationship with TCM consumption providing them a solution specifically designed to satisfy their needs. It is aiming to use TCM therapy to not only solve females’ health problems, but also improve females' life quality, even achieve longevity. We show in this business plan that our business are low capital requirement business that become quickly profitable and we do not need to have a loan. It should reach a turnover of 47,617€ and a profit of 4,130€ the first year.